58.6k views
3 votes
FIND x :

x+(x+1)+(x+2)=(x+1)^2
A. 1
B. 0
C. 3
D. 2

2 Answers

3 votes

Answer:

2

Explanation:

User Infinite
by
4.7k points
4 votes

Answer:

x = - 1, x = 2

Explanation:

Given

x + (x + 1) + (x + 2) = (x + 1)² ← expand using FOIL , then

x + x + 1 + x + 2 = x² + 2x + 1 , that is

3x + 3 = x² + 2x + 1 ( subtract 3x + 3 from both sides )

0 = x² - x - 2 ← in standard form

0 = (x - 2)(x + 1) ← in factored form

Equate each factor to zero and solve for x

x + 1 = 0 ⇒ x = - 1

x - 2 = 0 ⇒ x = 2

User Manish Thakur
by
4.7k points